2017
DOI: 10.1002/ejoc.201700102
|View full text |Cite
|
Sign up to set email alerts
|

Helical Folding of Hydroxy‐Substituted N‐Hetero‐ortho‐phenylenes Directed by Intramolecular Hydrogen Bonds

Abstract: Derivatives of the ortho‐phenylene hexamer containing pyridine moieties and hydroxy groups were prepared through Negishi cross‐coupling reactions between bis(chloropyridyl)biphenyl and alkoxy‐substituted arylzinc reagents. X‐ray diffraction analysis revealed a closed helical folding directed by π–π stacking and hydrogen bonds. No broadening or coalescence of 1H NMR peaks was observed between 213 and 313 K, which indicates the high stability of the helical folding in CDCl3 solution. DFT calculations on the rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…23,24 Our work has focused on the o-phenylenes, simple polyphenylenes 25 that adopt helical conformations in solution driven by (offset) arene-arene stacking interactions parallel to the helical axis. [26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our work has focused on the o-phenylenes, simple polyphenylenes 25 that adopt helical conformations in solution driven by (offset) arene-arene stacking interactions parallel to the helical axis. [26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties.…”
Section: Introductionmentioning
confidence: 99%
“… 34 o -Phenylenes offer an attractive combination of properties that complements those of other classes of aromatic foldamers based on hydrogen bonding. 4 , 6 They are of interest both as helical oligomers and polymers 32 , 35 39 and also as prototypical systems for other o -arylenes 40 44 and the broader class of sterically crowded polyphenylenes, 45 including oligo- and polynaphthalenes, 46 48 cages, 49 and other complex architectures. 50 54 …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, hydroxy groups were introduced to N-oP 6 at the orthopositions of the terminal phenylenes. [46] Intramolecular hydrogen bonds between the pyridine rings and hydroxy groups effectively stapled the helix and resolution of the (P)-and (M)helices were achieved by chiral HPLC. The stable helical folding inspired us to study chiral self-sorting by using dynamic macrocycles containing N-oP 6 moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike oP n s, N ‐oP 6 s take only the 3/1 helical conformation even in the solution state due to a strong antiparallel stacking of the pyridine rings. In a previous study, hydroxy groups were introduced to N ‐oP 6 at the ortho ‐positions of the terminal phenylenes [46] . Intramolecular hydrogen bonds between the pyridine rings and hydroxy groups effectively stapled the helix and resolution of the ( P )‐ and ( M )‐helices were achieved by chiral HPLC.…”
Section: Introductionmentioning
confidence: 99%